Raf/MEK/ERK pathway activation is required for Junín virus replication - Rodríguez, María Eugenia (2014)
In the present work we investigated the importance of the Raf/MEK/ERK signalling pathway in the multiplication of the arenavirus Junı´n (JUNV) in monkey and human cell cultures. We established that JUNV induces a biphasic activation of ERK and we proved that a specific inhibitor of the ERK pathway, U0126, impairs viral replication. Furthermore, U0126 exerted inhibitory action against the arenaviruses Tacaribe and Pichinde. Moreover, treatment with known ERK activators such as phorbol 12-myristate 13-acetate and serum increased viral yields whereas ERK silencing by small interfering RNAs caused the inhibition of viral multiplication. Therefore, activation of the Raf/MEK/ ERK signalling pathway is required to ensure efficient JUNV replication and may constitute a host target for the development of novel effective therapeutic strategies to deal with arenavirus infections.